A Novel Method for Frequency Estimation Considering Instrument Transient Effect - Mohsen Tajdinian; Mehdi Zareian Jahromi; Mojtaba Jalalpour (International Journal of Electrical and Computer Engineering (IJECE), 2015)
Large disturbances in power systems cause deviation in the frequency from the nominal value. Since the frequency is an important factor in the electrical network parameter measurements, it can cause malfunction of the protection system. In addition, Because of decaying DC and oscillatory components that introduced by CCVT in response of voltage variation during the fault occurrence, cause changes in the value of received voltage of primary side of CCVT. An improved least square method for estimating frequency is presented in this paper. In order to reduce the effect of this transient component, phasor estimation method has been improved by using the least square technique and utilizing knowledge of CCVT design. The capability of the proposed method was verified by several case studies generating signals in PSCAD/EMTDC. The results show the accuracy, speed and capability of the proposed method